Folk Songs as an Agent of Cultural Transmission, ​Teaching and Learning for a Yoruba Child - Ikumapayi Abayomi Ayoola (Accelerando: BJMD, 2023)
This study explores the origin, as well as the development and changes that might have occurred in the folk music in the course of time, and to transcribe African music materials into educational materials for school use. Significantly, the objective is to document the identified function and the performance practice, which would give insight into the performance of the music. It also documents and archives musical folk songs for educational purposes, in order to reveal its socio-cultural values within the context in which it is performed. The research design used was historical research method, library search to consult relevant scholarly works, newspapers, theses, books and journals, electronic sources such as the video clip, tape recording and internet were examined, and they provided additional information for the study. The study identifies and provides musical notation of Yoruba folk songs materials that can be interpreted globally in the world of music, and also examines the influence and efficacy of Yoruba folk songs in ways of teaching that would be geared towards supporting learning, inculcating moral standards and cultural transmission. The findings revealed that folk songs constitute a dynamic forum through which members of a society respond and adapt to the culture of the society. It therefore recommends that contemporary government should provide better funding to ensure preservation of such cultural institutions and heritage.